Durability characteristics of concrete using ferronickel slag fine aggregate and fly ash - Saha, A.; Sarker, Prabir (I C E Publishing, 2018)
The production process of ferronickel generates an enormous amount of slag (FNS) as a by-product, which has potential for use as a fine aggregate in concrete. However, information regarding the durability of FNS aggregate concrete is very limited in the literature. This study evaluates the durability characteristics of concrete using FNS as up to 100% replacement of natural sand and fly ash as 30% replacement of cement. The volume of permeable voids (VPV) of concrete was found to increase with the increase of FNS aggregate. As a result, sorptivity and chloride permeability showed increasing trends with the increase of FNS aggregate. However, the pozzolanic reaction of fly ash reduced the porosity of the concrete, as evidenced by scanning electron microscopy and energy-dispersive X-ray spectroscopy. The specimens with FNS aggregate and fly ash were classified as 'excellent' in terms of VPV, 'low' in terms of chloride permeability and 'good' in terms of sorptivity. The use of fly ash also reduced the strength losses of FNS aggregate concrete subjected to alternate wet-dry cycles. Overall, a durability equivalent to that of conventional concrete could be achieved when FNS was used as a partial replacement of sand together with fly ash as a partial replacement of cement.